Rubella virus seropositivity after infection or vaccination as a risk factor for multiple sclerosis - Ingvarsson, Jens; Grut, Viktor; Biström, Martin; Berg, Linn Persson; Stridh, Pernilla; Huang, Jesse; Hillert, Jan; Alfredsson, Lars; Kockum, Ingrid; Olsson, Tomas; Waterboer, Tim; Nilsson, Staffan; et al. (European journal of neurology, 2024)
Background Multiple sclerosis (MS) is a demyelinating disease affecting millions of people worldwide. Hereditary susceptibility and environmental factors contribute to disease risk. Infection with Epstein–Barr virus (EBV) and human herpesvirus 6A (HHV‐6A) have previously been associated with MS risk. Other neurotropic viruses, such as rubella virus (RV), are possible candidates in MS aetiopathogenesis, but previous results are limited and conflicting. Methods In this nested case–control study of biobank samples in a Swedish cohort, we analysed the serological response towards RV before the clinical onset of MS with a bead‐based multiplex assay in subjects vaccinated and unvaccinated towards RV. The association between RV seropositivity and MS risk was analysed with conditional logistic regression. Results Seropositivity towards RV was associated with an increased risk of MS for unvaccinated subjects, even when adjusting for plausible confounders including EBV, HHV‐6A, cytomegalovirus and vitamin D (adjusted odds ratio [AOR] = 4.0, 95% confidence interval [CI] 1.8–8.8). Cases also had stronger antibody reactivity towards rubella than controls, which was not seen for other neurotropic viruses such as herpes simplex or varicella zoster. Furthermore, we observed an association between RV seropositivity and MS in vaccinated subjects. However, this association was not significant when adjusting for the aforementioned confounders (AOR = 1.7, 95% CI 1.0–2.9). Conclusions To our knowledge, these are the first reported associations between early RV seropositivity and later MS development. This suggests a broadening of the virus hypothesis in MS aetiology, where molecular mimicry between rubella epitopes and human central nervous system molecules could be an attractive possible mechanism.